Knowledge, attitude, and practice about hygiene among livestock keepers in peri-urban area of vadodara district, Gujarat - Vaibhavi Khadayata; Divya Aggarwal (Wolters Kluwer Medknow Publications, 2020)
Background: Zoonoses are considered as an emerging public health problem. To reduce its prevalence, hygiene of animals as well as personal hygiene during milk production cycle is vital. This study has been conducted in the peri-urban areas of Vadodara district. Objective: The objective was to assess the knowledge, attitude, and practices (KAPs) about hygiene among livestock keepers in the peri-urban area. Materials and Methods: The study design is cross-sectional descriptive in nature mainly based on pretested questionnaires to answer questions on KAP with regard to hygiene among livestock keepers. A total of 100 livestock keepers were randomly selected from the peri-urban area of Vadodara. Results: Among the selected respondents, 28% of participants know that disease can transmit from animal to human. The majority 72% of all interviewed respondents had no knowledge that disease can transmit from animal to human. Only 33% livestock keepers had awareness that zoonotic disease can be prevented. Among all livestock keepers interviewed, about 52% showed positive attitude and 48% showed negative attitude toward hygiene. There was positive impact of good socioeconomic status on the practices about hygiene, as majority of livestock keepers with good practices belong to the upper middle group. Conclusion: This study indicates that education has impact on knowledge about zoonotic disease, its transmission, and how hygiene is important to prevent zoonotic disease. Further, there is a need to increase the awareness about hygiene among livestock keepers with regard to personal, animal, and milk hygiene.